Yoga for health with Jenny Cornero. - Cornero, Jenny (Kutir Films : Intavision Media, 2013)
Yoga with a slow pace, plus the long breathing techniques through Pranayama, helps dampen the causes of fears within one's mind, and thus reducing anxiety.--